STRATEGI PENGEMBANGAN MANAJEMEN SUMBER DAYA MANUSIA BAGI GENERASI MILLENIAL - WIWIT SETYO WARDANI; ROSADIANA, ALFIRA (JOURNAL KOPERASI DAN MANAJEMEN, 2025)
Purpose – The purpose of a human resource management development strategy for Millennials is to attract, retain, and motivate this key demographic. This involves tailoring HR practices to align with their values, expectations, and work styles, fostering a positive and engaging work environment, and providing opportunities for growth, development, and meaningful contributions. Ultimately, a well-defined strategy ensures a highly productive and committed Millennial workforce that drives organizational success. Design/methodology/approach – This research employs a qualitative approach, utilizing in-depth interviews and document analysis to explore effective Human Resource Management (HRM) strategies for engaging and retaining millennial employees. The study focuses on identifying key factors influencing millennial work preferences and subsequently proposing a tailored HRM framework designed to enhance their job satisfaction, productivity, and overall contribution to the organization. Findings – The study reveals key strategies for developing human resource management practices that effectively engage and retain Millennial employees. Findings emphasize the importance of personalized development opportunities, technology-driven communication, flexible work arrangements, and a strong focus on purpose and values alignment to foster a motivated and productive Millennial workforce. Research limitations/implications – This research, focusing on HRM development strategies for millennial employees, is limited by its single-industry scope and geographical specificity, potentially impacting the generalizability of findings. Future research should explore cross-industry comparisons and diverse regional contexts to validate and expand upon these strategies. Furthermore, longitudinal studies could assess the long-term effectiveness of the proposed HRM interventions on millennial engagement and organizational performance, offering more robust and actionable implications for practitioners. Originality/value – This paper examines strategies for developing human resource management (HRM) practices tailored to the needs and values of the Millennial generation. Its originality lies in synthesizing contemporary HRM trends with the specific characteristics of Millennials, offering practical recommendations for attracting, retaining, and motivating this crucial workforce segment. The value of this research lies in providing actionable insights for organizations seeking to optimize their HRM practices for enhanced performance and competitiveness in a Millennial-dominated labor market.